The impact of acute calcium intake on bone turnover markers during a training day in elite male rowers - Lundy, B.; McKay, A. K.; Fensham, N. C.; Tee, N.; Anderson, B.; Morabito, A.; Ross, M. L. R.; Sim, M.; Ackerman, K. E.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2023)
Introduction Although an acute exercise session typically increases bone turnover markers (BTM), the impact of subsequent sessions and the interaction with preexercise calcium intake remain unclear despite the application to the "real-life" training of many competitive athletes.